2016
DOI: 10.1108/md-09-2015-0400
|View full text |Cite
|
Sign up to set email alerts
|

Why do firms adopt enterprise risk management (ERM)? Empirical evidence from France

Abstract: Purpose Enterprise risk management (ERM) is a risk management approach that calls for integrating all the organization-wide risks and takes a portfolio view point of managing organizational risks. The purpose of this paper is to investigate the factor that influence a firm’s decision to adopt ERM. Design/methodology/approach The authors employ a particular technique of survival data analysis, the Cox proportional hazards model, to investigate the factors that lead towards the decision of initiating an ERM pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 49 publications
2
41
0
10
Order By: Relevance
“…SMEs, due to the lack of management capabilities and lack of resources, are more likely focused on ERM practices. In fact, ERM practices enable a firm to reduce different types of costs associated with firms' operational and non-operational activities (Khan et al 2016). However, in contrast, many small firms are unable to support risk management activities due to lack of resources and capabilities (Brustbauer 2016).…”
Section: (Committee Of Sponsoring Organizations Of the Treadway Commimentioning
confidence: 99%
“…SMEs, due to the lack of management capabilities and lack of resources, are more likely focused on ERM practices. In fact, ERM practices enable a firm to reduce different types of costs associated with firms' operational and non-operational activities (Khan et al 2016). However, in contrast, many small firms are unable to support risk management activities due to lack of resources and capabilities (Brustbauer 2016).…”
Section: (Committee Of Sponsoring Organizations Of the Treadway Commimentioning
confidence: 99%
“…ERM has a positive influence on firm performance (Callahan and Soileau 2017). ERM practices let companies to reduce various types of costs related to companies' operational and non-operational activites (Khan et al 2016). Berry-Stölzle & Xu (2018) showed that ERM is not limited to cost reduction, still it is associated with many strategic positions for companies that might directly or indirectly affect company results also.…”
Section: Factors Influencing Firm Performancementioning
confidence: 99%
“…На открытых горных рабо тах рост объемных показателей достигался повышением производительности горнотранспортного оборудования (экскаваторов и самосвалов) (рис. 3,4,5). Рис 12 МАРТ, 2020, "УГОЛЬ" РЕГИОНЫ Ускоренная отработка запасов требует значительных усилий для их своевременной подготовки.…”
Section: перспективы угольной промышленностиunclassified
“…Конструктивно анкеры АК01-25 имеют ряд отличий от применя емых анкеров АК01. Кроме увеличенной несущей способности до 250 кН их главным преимуществом является возможность приме нения гайки-подвеса, что позволяет использовать анкеры для уси ления крепи горной выработки в сочетании с креплением подвес ной монорельсовой дороги [4].…”
Section: основная частьunclassified
See 1 more Smart Citation